Aqueous-phase hydrogenolysis of glucose to value-added chemicals and biofuels: A comparative study of active metals. (January 2015) - Liu, Chengwei; Zhang, Chenghua; Liu, Kangkai; Wang, Yi; Fan, Gaixian; Sun, Sikai; Xu, Jian; Zhu, Yulei; Li, Yongwang
Abstract: Glucose is the most abundant platform molecule of biomass in nature. High value-added chemicals and liquid fuels can be obtained by selectively breaking C–C/C–O bonds and removing surplus oxygen in glucose. This article focuses on glucose hydrogenolysis over a wide variety of transition metal catalysts (Cu/C, Ni/C, Pt/C, Pd/C, Ru/C, Rh/C, Ir/C). Liquid and gas phase after reaction mainly contain three types of products such as polyols, alkanes, furans. Many value-added chemicals and liquid fuels were obtained, such as sorbitol, 1, 2-propanediol, ethylene glycol, 2, 5-dimethylfuran, 2, 5-dimethyltetrahydrofuran, hexane, etc. Different metal catalysts showed different selectivities to these products. Typically, at hydrogenation conditions of 453 K and 4.0 MPa, glucose was largely converted to C1 products over the Ru/C catalyst. Pd/C selectively converted glucose into C2 and C3 products. C6 products were most selective over Pt/C. The hydrogenation/hydrogenolysis capabilities of different metals for C–C and C–O bonds, the endocyclic CC and C–O–C bonds are also quite different. For example, Pt/C provides the weakest hydrogenolysis activity to C–O and C–C bonds. Ru/C possesses the highest activity to C–C and C–O bond cleavage. Meanwhile, it is most active for C–O–C bond hydrogenation in glucose at low temperature. Cu/C exhibits the weakest endocyclic CC bond hydrogenation activity in furan ring. The reaction pathway of glucose hydrogenolysis over different metal catalysts was also outlined. Graphical abstract: Highlights: This work studied the hydrogenolysis of glucose over different transition metal catalysts. Ru/C had higher activity for C1 products; Pd/C had higher selectivities to C2 and C3 ; Pt/C was more selective to C6 products. Ru/C shows the highest C–C and C–O bond cleavage activity, Pt/C exhibits the weakest activity to C–C and C–O bond cleavage.